2002
DOI: 10.1091/mbc.01-03-0116
|View full text |Cite
|
Sign up to set email alerts
|

Hyphal Elongation Is Regulated Independently of Cell Cycle inCandida albicans

Abstract: The mechanism for apical growth during hyphal morphogenesis in Candida albicans is unknown. Studies from Saccharomyces cerevisiae indicate that cell morphogenesis may involve cell cycle regulation by cyclin-dependent kinase. To examine whether this is the mechanism for hyphal morphogenesis, the temporal appearance of different spindle pole body and spindle structures, the cell cycle-regulated rearrangements of the actin cytoskeleton, and the phosphorylation state of the conserved Tyr19 of Cdc28 during the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
138
1
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(164 citation statements)
references
References 48 publications
18
138
1
7
Order By: Relevance
“…3D). Hyphae initiated from unbudded G 1 cells gave rise to germ tubes without constriction at the base of germ tube, whereas hyphae initiated from budded cells (non-G 1 cells) generated elongated buds with a constriction (25). Our results suggest that release from farnesol inhibition promotes Nrg1 degradation through transient activation of SOK1 expression for hyphal initiation.…”
Section: Sok1 Expression Is Activated On Release From Farnesol Inhibimentioning
confidence: 73%
“…3D). Hyphae initiated from unbudded G 1 cells gave rise to germ tubes without constriction at the base of germ tube, whereas hyphae initiated from budded cells (non-G 1 cells) generated elongated buds with a constriction (25). Our results suggest that release from farnesol inhibition promotes Nrg1 degradation through transient activation of SOK1 expression for hyphal initiation.…”
Section: Sok1 Expression Is Activated On Release From Farnesol Inhibimentioning
confidence: 73%
“…These two organisms are well known to differ in the number of ARN genes, specificity for siderophores, and ability in siderophore production. A similar situation is the ability of C. albicans (but not S. cerevisiae) to shift a dynamic cell cycle-dependent distribution of a pool of actin toward a persistent localization at the hyphal tips when cells switch growth from the yeast form to the filamentous form (48). Then, what is the relationship between the CaArn1p molecules in the two locations?…”
Section: Figmentioning
confidence: 95%
“…The GFP-tagged CaCDC5-regulated strain (CB112), however, was somewhat more sensitive to the absence of CaCdc5p than strain CB104, as the filaments were shorter in length at the various time points. The majority of cells from strain CB112 depleted of CaCdc5p for 3 h were elongated or large doublets ( Figure 4A; Table 5) and contained spindles in the form of distinct spots or two spots side by side, corresponding to unseparated spindle pole bodies or very short spindles in S-G2 phases of the cell cycle (Barton and Gull, 1988;Hazan et al, 2002). Despite the elongated and large doublet morphology of cells at 3 h, only 2.2% of the population contained an extended mitotic spindle.…”
Section: Cacdc5p Is Required For Spindle Elongationmentioning
confidence: 99%
“…In filamentous and dimorphic fungi, the connection between cell cycle factors and true hyphal growth is less clear. Hyphae continue to grow whether their apical-most nuclei are in interphase or mitosis (Kron and Gow, 1995), and it was recently demonstrated that the duration of cell cycle stages was similar in yeast, germlings, and apical hyphal cells of C. albicans (Hazan et al, 2002). However, the coordination between nuclear localization, division, and septation with the initiation and maintenance of hyphal growth in Candida requires a relationship between aspects of the cell cycle and hyphal growth.…”
Section: Introductionmentioning
confidence: 99%